FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN (Students' Journal of Accounting and Banking, 2015)
This research is a study that tested the effect of audit quality, financial condition, Audit Opinion Previous Year, Company Size, Debt defaults on acceptance Going Concern on manufacturing companies listed in Indonesia Stock Exchange. In this study, researchers used a purposive sampling and obtained samples of 65 companies listed on the Stock Exchange in 2010-2012. The analytical method used is logistic regression. The results of this study indicate Quality Audit, Financial Condition and company size does not affect the going concern opinion revenues while the previous year's audit opinion and Debt Default affect the acceptance of going concern opinion.Keywords: Going Concern, Quality Audit, Financial Condition, Audit Opinions Prior Year, Company Size, Debt Default